Leak detection in pipelines using ensemble empirical mode decomposition - Mohd Firdhaus, Ahmad (2013)
This thesis is discusses the techniques of leak detection in pipe system by using “Ensemble Empirical Mode Decomposition” method (EEMD). Effective leak detection is important to prevent leaks in pipes, particularly involving irrigation and drainage industry. Delay in detecting leaks can result an economic losses and environmental damage. In this study, water is used as the main medium and MDPE and GI was used. Wave propagation will be analyzed in the EEMD and the results of the analysis in the pipe with and without leakage will be compared. To detect the signal wave in the pipe, strain gauge pressure transducer and piezoelectric sensor was used. Transient signal that triggered by an automatic solenoid valve was used as a reference of the presence of a leak in the wave signal data in a particular period. The results of the analysis were successfully demonstrated by the presence of a leak in the pipe MDPE and GI in certain period and for a particular sample size. From the results, it can be concluded that the GI pipes is easier to analyzed compared to MDPE pipe. This is because the speed of wave in GI pipes is higher and had more superficial wave propagation.